A fluorescent dye with large Stokes shift and high stability: synthesis and application to live cell imaging. Issue 13 (25th January 2017) - Gao, Zheng; Hao, Yongcao; Zheng, Meiling; Chen, Yi
Abstract : A new fluorescent dye with large Stokes shift and excellent photo-stability for live cell imaging has been developed. Abstract : A fluorescent dye, 2, 5-bis(6-amine-benzoxazol-2-yl)thiophene (BBTA ), was synthesized by a two-step reaction from starting material 2, 5-bis(benzoxazol-2-yl)thiophene (BBT ).BBTA exhibited strong emission and large Stokes shift in solvent, and the largest Stokes shift (Δ λ = 186 nm or Δ ν = 8572 cm −1 ) was obtained in buffer solution (PBS, pH = 7.2) with 5% (v/v) of polyethylene glycol monomethyl ether (mPEG550, MW = 550) as additive. Application ofBBTA to live cell imaging showed thatBBTA was clearly expressed in mitochondria with high contrast. Besides, BBTA showed low cytotoxicity and excellent photo-stability.